THE DOMESTICATION OF GENRE. NAJÎB MAHFÛZ AND THE WESTERN NOVEL - Hamarneh, Walid (Surfaces, 1991)
An account of the ways in which Mahfûz domesticates the generic conventions of the Western novel in the Egyptian context. Survey of the writings of Mahfûz.